2023
DOI: 10.3390/ma17010184
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Simulation on Solidification during Vertical Centrifugal Casting Process for TC4 Alloy Wheel Hub with Enhanced Mechanical Properties

Yujie Yang,
Xiangyi Wang,
Xiangming Li
et al.

Abstract: The Ti-6Al-4V (TC4) alloy wheel hub has exhibited some defects that affect the properties during the vertical centrifugal casting process. Therefore, the analysis of the solidification process would contribute to solving the above-mentioned problems. In this study, an orthogonal experimental design was employed to optimize the process parameters (rotational speed, mold preheating temperature, and pouring temperature) of the vertical centrifugal casting method. The effects of process parameters on the velocity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…In order to improve the castability of titanium melt, filed-assisted casting techniques have been developed to fabricate near-net-shape parts with complex structures. However, their coarse microstructure and inevitable casting defects such as porosity, shrinkage, and ceramic inclusions can worsen the properties of the cast alloys and/or components [ 6 , 8 , 9 ]. Feng et al [ 10 ] reported that large-size Ti-6Al-4V thin-wall casing could be successfully fabricated by centrifugal casting, and the effects of mold pre-heating temperatures and the hot isostatic pressing (HIP) process on the microstructural characteristics and mechanical properties.…”
Section: Introductionmentioning
confidence: 99%
“…In order to improve the castability of titanium melt, filed-assisted casting techniques have been developed to fabricate near-net-shape parts with complex structures. However, their coarse microstructure and inevitable casting defects such as porosity, shrinkage, and ceramic inclusions can worsen the properties of the cast alloys and/or components [ 6 , 8 , 9 ]. Feng et al [ 10 ] reported that large-size Ti-6Al-4V thin-wall casing could be successfully fabricated by centrifugal casting, and the effects of mold pre-heating temperatures and the hot isostatic pressing (HIP) process on the microstructural characteristics and mechanical properties.…”
Section: Introductionmentioning
confidence: 99%